Prevalence of systemic risk factors in chronic periodontitis patients at Haji regional public hospital in East Java Province: a cross-sectional study - Nilawati, Nina; Sumekar, Henu; Nafiah, Nafiah; Rizal, Moh. Basroni (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2025)
Introduction: Periodontal disease is a chronic inflammatory disease that affects the tooth-supporting tissues  and is often associated with various systemic disorders. Understanding this relationship is essential for comprehensive dental management. The aim of this study was to determine the prevalence of systemic risk factors among patients with chronic periodontitis at Haji Regional Public Hospital, East Java Province. Methods: A descriptive observational study with a cross-sectional design involving 108 patients diagnosed with chronic periodontitis. Data were collected from electronic medical records and analyzed descriptively using cross-tabulation. Results: The majority of patients were older adults (51.9%) and female (59.3%). A total of 78.7% had systemic conditions, the most common being hypertension and diabetes mellitus. Conclusion: Most chronic periodontitis patients had systemic conditions, particularly among older adults. These findings emphasize the importance of an interdisciplinary approach in periodontal care.Prevalensi faktor risiko sistemik pada pasien periodontitis kronis di Rumah Sakit Umum Daerah Haji Provinsi Jawa Timur: Studi cross sectional Pendahuluan: Penyakit periodontal merupakan penyakit inflamasi kronis yang memengaruhi jaringan penyangga gigi dan sering kali berhubungan dengan berbagai gangguan sistemik. Memahami hubungan ini sangat penting untuk penatalaksanaan kedokteran gigi yang komprehensif. Penelitian ini bertujuan untuk mengetahui prevalensi faktor risiko sistemik pada pasien dengan periodontitis kronis di Rumah sakit Umum Daerah Haji Provinsi Jawa Timur. Metode: Penelitian observasional deskriptif dengan desain potong lintang yang melibatkan 108 pasien yang didiagnosis dengan periodontitis kronis. Data dikumpulkan dari dokumentasi medis elektronik dan dianalisis secara deskriptif menggunakan tabel krostab. Hasil: Mayoritas pasien berusia lanjut (51,9%) dan berjenis kelamin perempuan (59,3%). Sebanyak 78,7% memiliki kondisi sistemik, yang paling umum adalah hipertensi dan diabetes melitus. Simpulan: Sebagian besar pasien dengan periodontitis kronis memiliki kondisi sistemik, terutama pada kelompok usia lanjut. Temuan ini menekankan pentingnya pendekatan interdisipliner dalam perawatan periodontal.